The Role of Agreeableness and Self-esteem on Fear of Missing Out - Sholihat, Suvianti; Abdul Rahman, Agus; Sudirman, Deden; Azizah, Nur’aini (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the interaction between agreeableness personality type, self-esteem, and fear of missing out in college students. This study useda quantitative approach with the correlational method. The data was collected using the Big Five Inventory, SLCS-R, and the Fear of Missing Out Scale. The participants were 536 college students in Bandung. The results of this study show that agreeableness and self-esteem can affect fear of missing out. Those who have agreeableness personality and low self-esteem are more prone to experience fear of missing out than those who have not. Furthermore, self-esteem can moderate the relationship between agreeableness and fear of missing out. Thus, this study highlights the influence of personality and self-esteem on fear of missing out.